Aryl-substituted dimethylbenzimidazolines as effective reductants of photoinduced electron transfer reactions. Issue 34 (26th August 2015) - Hasegawa, Eietsu; Ohta, Taku; Tsuji, Shiori; Mori, Kazuma; Uchida, Ken; Miura, Tomoaki; Ikoma, Tadaaki; Tayama, Eiji; Iwamoto, Hajime; Takizawa, Shin-ya; Murata, Shigeru
Abstract: Photoinduced electron transfer (PET) reactions promoted by 2-aryl substituted 1, 3-dimethylbenzimidazolines (Ar-DMBIH) were investigated. Excited states of Ar-DMBIH, formed by irradiation using light above 360 nm, initiate PET reductions of various organic substrates, including transformations of epoxy ketones to aldols, free radical rearrangements such as the Dowd-Beckwith ring-expansion and 5- exo hexenyl cyclization, deprotection of N -sulfonyl-indols, and allylation of acyl formates. In these processes, Ar-DMBIH possessing 1-naphthyl, 2-naphthyl, 1-pyrenyl and 9-anthryl substituents formally act as two electron and one proton donors while the hydroxynaphthyl substituted derivative serves as a two electron and two proton donor. On the basis of the results of absorption spectroscopy studies, cyclic voltammetry and DFT calculation, a mechanistic sequence for these reduction reactions is proposed that involves initial photoexcitation of the aryl chromophore of the Ar-DMBIH followed by single electron transfer (SET) to the organic substrate to generate the radical cation of benzimidazoline and the radical anion of the substrate. Graphical abstract: